MicroRNA-34A inhibits the growth, invasion and metastasis of gastric cancer by targeting PDGFR and MET expression - Peng, Yang (Portland Press Ltd., 2014)
Within the family of RTKs (receptor tyrosine kinases), PDGFR (platelet-derived growth factor receptor) has been implicated in carcinogenesis and tumour development. miRNAs (microRNAs), which can target the mRNAs (messenger RNAs) of cancer-associated genes, are abnormally expressed in various cancers. In this study, our aim was to identify the miRNAs that target PDGFR-α/β and to study the functions of these miRNAs. miR-34a was predicted to target PDGFR, and luciferase reporter assays showed that miR-34a could directly target PDGFR. Meanwhile, we found that miR-34a was down-regulated in gastric cancer tissues and was associated with metastasis. Our findings showed that miR-34a could inhibit gastric cancer cell migration, invasion and proliferation, but these tumourigenic properties were only partially restored when PDGFR-α/β was overexpressed. In subsequent experiments, we found that the overexpression of both PDGFR and MET could completely restore the gastric cancer tumourigenic properties. Moreover, the cancer-associated cell signalling pathway was studied, and we found that miR-34a could inhibit Akt [PKB (protein kinase B)] phosphorylation, which was restored by the overexpression of both PDGFR and MET. In conclusion, miR-34a may act as a potential tumour suppressor in gastric cancer and is associated with the mechanisms of gastric cancer metastasis; miR-34a can inhibit gastric cancer tumourigenesis by targeting PDGFR and MET through the PI3K (phosphoinositide 3-kinase)/Akt pathway.